2021
DOI: 10.2355/isijinternational.isijint-2021-140
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Effects on the Migration of Nanoscale Cavities in Iron

Abstract: Accurate knowledge of the influence of hydrogen on the behavior of vacancies and vacancy clusters is crucial for understanding the mechanism of hydrogen embrittlement of α-iron and its alloys. Using in-situ transmission electron microscopy, we examined the effects of hydrogen on the behavior of nanoscale cavities under heating, by comparison between the behaviors of cavities without hydrogen produced upon high-energy electron irradiation and those with hydrogen produced upon electro-deposition. It is revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has also been found that the interaction between H and vacancy-clusters has not followed the pattern if extrapolating from V 1 H; perhaps the most interesting behaviour is the reduction in diffusion barrier, upon introduction of H into the larger clusters V 4 H and V 5 H. A similar phenomenon, dubbed the hydrogen lubrication effect, has been explored computationally in FCC metals [80]. If this trend continues and the gap continues to increase, it could help to explain the experimentally observed H-induced nano-void migration [81] and could have implications for HE by contributing towards vacancy agglomeration during the HESIV mechanism [14,82,83]. A similar atomic mechanism that lowers the diffusion barrier for Vacancy-H complexes could be responsible for the predicted increase in dislocation velocity/mobility [84,85], which could directly support the HELP mechanism [9] of HE.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that the interaction between H and vacancy-clusters has not followed the pattern if extrapolating from V 1 H; perhaps the most interesting behaviour is the reduction in diffusion barrier, upon introduction of H into the larger clusters V 4 H and V 5 H. A similar phenomenon, dubbed the hydrogen lubrication effect, has been explored computationally in FCC metals [80]. If this trend continues and the gap continues to increase, it could help to explain the experimentally observed H-induced nano-void migration [81] and could have implications for HE by contributing towards vacancy agglomeration during the HESIV mechanism [14,82,83]. A similar atomic mechanism that lowers the diffusion barrier for Vacancy-H complexes could be responsible for the predicted increase in dislocation velocity/mobility [84,85], which could directly support the HELP mechanism [9] of HE.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the fracture process is significantly influenced by vacancies, representing a crucial and decisive factor from this perspective 11,12) . Moreover, the recent study investigated the relationship between local H concentration and vacancy formation energies, focusing on the observed phenomenon of superabundant vacancy formation 13) . It was found that regions characterized by high hydrogen concentrations demonstrated significantly reduced vacancy formation energies, providing support for the experimentally observed superabundance of vacancies.…”
Section: Introductionmentioning
confidence: 99%